Evaluación de la Huella Hídrica del Banano en la Provincia de Los Ríos, 2018 - Fernández Guayasamín, Aldaír Vicente (2018)
This research study focuses on the environmental problems of water resources regarding the excessive consumption and contamination of water that currently generate the banana industry in the province of Los Ríos. The methodology that was used is the calculation of the water footprint to determine the environmental impact on the water caused that are carried out in the agricultural phase of the banana plantations. Due to the entrance restrictions to the banana plantations, the stratum of the banana sample in the region could not be met, therefore, the study was carried out in 22 banana plantations distributed in nine cantons of the province of Los Ríos. The impact generated by the banana plantations is not only environmental, but there are other factors such as the social and economic factors involved due to the harmful effects they produce in the agricultural phase, which is the one that consumes the most water through the irrigation processes. , since it is watered every day, six days a week, generally in the dry season (May to November) and two to three days a week in the dry season. The atmospheric factors such as temperature, precipitation directly affect the calculation of the evapotranspiration of the crop, which oscillate between 18 ºC to 31 ºC, and 1250 to 2000 mm / year respectively, in the days of highest reference precipitation, the crop took more advantage the amount of water available in the soil for the plant. For this reason, an environmental diagnosis was carried out with the physical, biotic and sociocultural components in order to know in a more sensitive way the current state of these factors, and to determine good environmental management for water in banana production. The average yield is 58.9 Ton / Ha of the banana production in the banana plantations and is related to the total water footprint whose averages are 404.6 m3 / Ton (blue) 486.7 m3 / Ton (green) and 37.8 m3 / Ton (gray) , since the values of these, diminished considerably when the yield of the production increased. The management of water resources within the banana plantations constitutes the set of strategies established according to the environmental diagnosis, the water footprint, the yield of the banana production, and the systems implemented for the irrigation of the crop, with the objective of reducing the volumes of the water footprint in each of the banana plantations and guarantee the efficient use of the water used in the agricultural phase for banana production.